Challenges to Journalists Working in Pakistan and Indian administered Kashmir: A Case Study of Muzaffarabad & Srinagar - Shah, Syed Mubashar Hussain; Dr. Babar Hussain Shah,; Qurat ul Ain, (Journal of Peace, Development and Communication, 2021)
Kashmir, an unresolved and longstanding dispute is among the most complicated global conflicts in present world. Due to heavy military and paramilitary deployment and high number of civilian casualties in the disputed region, issues of human rights abuses are matter of great concern for the international community and global human rights bodies. Media, a sole source of information in the conflict zone and a watchdog in a society highlighting these human rights violations and in result facing multiple challenges like censorships, threats and target killings by the parties involved in the conflict. This study aims to explore the situation of freedom of press, challenges and capacity issues of the journalists on both sides of Line of Control (LoC) in reporting context. In this study 73 journalists were interviewed through semi-structured questionnaire out of them 15 respondents were belonging to Srinagar, Indian administered Kashmir (IaK) while 58 from Muzaffarabad, Pakistan administered Kashmir (PaK). Results showed that journalists working in IaK were facing more serious challenges than journalists in PaK. These challenges were included unfavorable media environment, abusive treatment and violence, threats to their lives and livelihood and anti-media laws. Moreover, journalists from both sides of LoC are struggling in access to information particularly from state institutions. The study revealed that journalists working on both sides of LoC were not being adequately trained on safety issues in conflict zone.